Life Cycle and Consumption Behavior from Islamic Economic Perspective - Aisyah Kartini (Saqifah: Jurnal Hukum Ekonomi Syariah, 2024)
The relationship between individual life cycles and consumption behavior. The life cycle, which includes stages such as childhood, adolescence, young adulthood, adulthood and older people, significantly impacts consumption patterns. The research aims to analyze the concept of life cycle and consumption behavior from an Islamic economic perspective. This type of research is classified as qualitative research. Primary data was obtained through interviews with 17 Muslim people in West Pasaman Regency. Data sender was obtained from books and journals related to the Islamic economic perspective's life cycle and consumption behavior. The results of this study show that each stage of life is characterized by different needs, priorities and income levels, which directly influence consumption decisions, for example, those aged 10 to 15 years consume more fast food without paying attention to health. In productive age, there is a difference in a person's consumption level, namely that some of them consume more by prioritizing desires than needs and others prioritize saving and buying goods according to their needs. When you are no longer productive, you are more likely to save money for future needs. From an Islamic economic perspective, consumption cannot be excessive and must be in accordance with Islamic consumption principles.